ACUTE BACTERIAL TUBULOINTERSTITIAL NEPHRITIS OF RENAL ALLOGRAFT COMPLICATED BY SEPTIC SHOCK - M. Krstic; A. V. Vatazin; E. I. Prokopenko; A. B. Zulkarnaev; E. S. Stolyarevich; R. O. Kantaria (Вестник трансплантологии и искусственных органов)
Herein we present the clinical case, which demonstrates the difficulties of the differential diagnosis of renal allograft damage. The importance of using of modern methods of diagnosis and treatment of urinary system in- fection after cadaveric kidney transplantation: computed tomography, graft tissue biopsy and timely application of the extracorporeal endotoxin selective adsorption are emphasized.